Associations between hemodynamic parameters at rest and exercise capacity in patients with implantable left ventricular assist devices. Issue 3 (March 2021) - Kondo, Toru; Okumura, Takahiro; Oishi, Hideo; Arao, Yoshihito; Kato, Hiroo; Yamaguchi, Shogo; Kuwayama, Tasuku; Haga, Tomoaki; Yokoi, Tsuyoshi; Hiraiwa, Hiroaki; Fukaya, Kenji; Sawamura, Akinori; et al.
Background: Hemodynamic parameters at rest are known to correlate poorly with peak oxygen uptake (VO2 ) in heart failure. However, we hypothesized that hemodynamic parameters at rest could predict exercise capacity in patients with left ventricular assist device (LVAD), because LVAD pump rotational speed does not respond during exercise. Therefore, we investigated the relationships between hemodynamic parameters at rest (measured with right heart catheterization) and exercise capacity (measured with cardiopulmonary exercise testing) in patients with implantable LVAD. Methods: We performed a retrospective medical record review of patients who received implantable LVAD at our institution from November 2013 to December 2017. Results: A total of 20 patients were enrolled in this study (15 males; mean age, 45.8 years; median duration of LVAD support, 356 days). The mean peak VO2 and cardiac index (CI) were 13.5 mL/kg/min and 2.6 L/min/m 2, respectively. CI and hemoglobin level were significantly associated with peak VO2 (CI: r = 0.632, p = 0.003; hemoglobin: r = 0.520, p = 0.019). In addition, pulmonary capillary wedge pressure, right atrial pressure, and right ventricular stroke work index were also significantly associated with peak VO2 . In multiple linear regression analysis, CI and hemoglobin level remained independent predictors of peak VO2 (CI: β = 0.559, p = 0.006; hemoglobin: β = 0.414, p = 0.049). Conclusions: CI at rest and hemoglobin level are associated with poor exercise capacity in patients with LVAD.